ANALYSIS OF IMMEDIATE AND REMOTE RESULTS OF TRADITIONAL TREATMENT METHODS AND THE CHRONOLOGY OF RECURRENCE OF CROHN'S DISEASE - Sattorov Zhasur Elmurodovich (Innovate Conferences, 2025)
Traditional approaches to the treatment of Crohn's disease in 57.1% of cases are accompanied by the development of postoperative complications, among which parastomal types (33.3%) and wound infection (25%) prevail, leading to a high frequency (31%) of unsatisfactory immediate treatment results.
Keywords: crohn's disease, the traditional method.